Intramedullary tissue cultures from the Reamer‐Irrigator‐Aspirator system for diagnosing fracture‐related infection. Issue 2 (10th August 2020) - Onsea, Jolien; Pallay, Jan; Depypere, Melissa; Moriarty, Thomas Fintan; Van Lieshout, Esther M.M.; Obremskey, William T.; Sermon, An; Hoekstra, Harm; Verhofstad, Michael H.J.; Nijs, Stefaan; Metsemakers, Willem‐Jan
Abstract: Fracture‐related infection (FRI) is a serious complication following musculoskeletal trauma. Accurate diagnosis and appropriate treatment depend on retrieving adequate deep tissue biopsies for bacterial culture. The aim of this cohort study was to compare intraoperative tissue cultures obtained by the Reamer‐Irrigator‐Aspirator system (RIA)‐system against standard tissue cultures obtained during the same surgical procedure. All patients had long bone fractures of the lower limbs and were assigned to the FRI or Control group based on the FRI consensus definition. The FRI group consisted of 24 patients with confirmed FRI and the Control group consisted of 21 patients with aseptic nonunion or chronic pain (in the absence of other suggestive/confirmatory criteria). Standard tissue cultures and cultures harvested by the RIA‐system showed similar results. In the FRI group, standard tissue cultures and RIA cultures revealed relevant pathogens in 67% and 71% of patients, respectively. Furthermore, in four FRI patients, cultures obtained by the RIA‐system revealed additional relevant pathogens that were not found by standard tissue culturing, which contributed to the optimization of the treatment plan. In the Control group, there were no false‐positive RIA culture results. As a proof‐of‐concept, this cohort study showed that the RIA‐system could have a role in the diagnosis of FRI as an adjunct to standard tissue cultures. Since scientific evidence on the added value of the RIA‐system in the management of FRI is currently limited, further research on this topic is required before its routine application in clinical practice.